Preparation, optimization and cellular uptake study of tanshinone I nanoemulsion modified with lactoferrin for brain drug delivery. (14th September 2019) - Wu, Yumei; Zhang, Bing; Kebebe, Dereje; Guo, Lili; Guo, Hong; Li, Nan; Pi, Jiaxin; Qi, Dongli; Guo, Pan; Liu, Zhidong
Abstract: Tanshinone I (TSI) is one of the bioactive compound obtained from the root of Salvia miltiorrhiza which is a well-known traditional Chinese medicine (TCM) used for the treatment of various diseases. Although TSI possesses several pharmacological effects, it has poor water solubility, blood–brain barrier (BBB) permeability and brain bioavailability. Therefore, in the present study, we developed TSI nanoemulsion (TSI-NE) modified with a brain targeting ligand (Lactoferrin (Lf)) to improve the BBB permeability. Pseudo-ternary phase diagrams were used to optimize the formulation. The optimal TSI-NE and TSI-Lf-NE were prepared and characterized. Finally, the uptake of TSI-Lf-NE by mouse brain microvascular endothelial cell line (bEnd.3 cells) was assessed using Coumarin-6 as a fluorescent probe. The results of the study showed that the stable optimal formulation of O/W nanoemulsion was successfully developed and modified with Lf. The cellular uptake study has shown that the fluorescence intensity (FI) increased with time over the incubation period. The FI at all time intervals increased in the following order: Coumarin-6-Solution＜Coumarin-6-NE＜Coumarin-6-Lf-NE. The results suggest that the BBB permeability of Coumarin-6-Lf-NE was better than those of Coumarin-6-NE and Coumarin-6 solution. Lf modified nanoemulsion has great potential for improving the brain delivery of TSI.